1998
DOI: 10.1083/jcb.140.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dimers of Dimers of Human Leukocyte Antigen (HLA)–DR on the Surface of Living Cells by Single-Particle Fluorescence Imaging

Abstract: The technique of single-particle fluorescence imaging was used to investigate the oligomeric state of MHC class II molecules on the surface of living cells. Cells transfected with human leukocyte antigen (HLA)–DR A and B genes were labeled at saturation with a univalent probe consisting of Fab coupled to R-phycoerythrin. Analysis of the intensities of fluorescent spots on the cell surface revealed the presence of single and double particles consistent with the simultaneous presence of HLA-DR heterodimers and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 46 publications
4
33
1
Order By: Relevance
“…However, it is possible that the peptide maps reflected the composition of the MHC class II molecules and not that of MHC class II-associated peptides. Spontaneous MHC class II association has also been suggested by single-particle fluorescence imaging and scanning force microscopy using living cells (16,31). However, the data reported here (Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, it is possible that the peptide maps reflected the composition of the MHC class II molecules and not that of MHC class II-associated peptides. Spontaneous MHC class II association has also been suggested by single-particle fluorescence imaging and scanning force microscopy using living cells (16,31). However, the data reported here (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…High-molecularmass bands containing MHC class II molecules in Western blots of murine and human cell lysates have been interpreted as preformed MHC class II double dimers (12)(13)(14)(15). Furthermore, using biophysical techniques, preformed double dimers have been described in MHC class II-transfected mouse fibroblasts (16). However, the conclusion from experiments involving soluble MHC class II and TCR molecules was that dimerization/oligomerization was driven by cognate interactions between the TCR and MHC class II:peptide complexes (4).…”
mentioning
confidence: 99%
“…SPFI allows visualization of individual molecules at the cell surface within a spatial resolution of ϳ25 nm (31). This technique permits the determination of positional information of molecules and the single diffraction limited spot intensity determines the number of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The SPFI methodology has previously been used to investigate molecules on the cell surface, in adherent cell lines grown in culture, where it is possible to locate the focal plane of single molecules at the cell surface (30,31). When adapting SPFI methodology for this study, it was found that focusing on single particles on embryo blastomeres was difficult due to the large three-dimensional shape of the cells.…”
Section: Spfi To Investigate the Spatial Distribution Of Hla-g In Prementioning
confidence: 99%
“…Both FPR 26,28,53 and SPT 30,54,55 studies have shown that the MHC protein is a highly mobile cell surface receptor, and its mobility is in part determined by its cytoplasmic tail. FRET [56][57][58] and single-molecule fluorescence imaging 59 studies have shown that MHC proteins also reorganize into oligomeric clusters. The lateral mobility of the lymphocyte receptor CD2 has been examined by FPR and SPT.…”
mentioning
confidence: 99%